Ensino, pesquisa, extensão: um estudo de caso na universidade federal rural do semi-árido, no estado do rio grande do norte - Santos, Érica dos (2019)
Teaching, research and extension are the pillars which sustain a university, they are constitutionally guaranteed to be inseparable, and none of them should be superimposed on the other in terms of treatment and relevance. The objective of this research was to analyze the university scenario regarding the teaching participation in the teaching, research and extension pillars at the Federal Rural University of Semi-Arid. For this purpose, it was proposed to identify the number of teachers performing teaching, research and extension activities, in order to sketch an overview showing the distribution of teachers in these three university pillars; compare the distribution of teachers on the university tripod by IFES campus; and to verify the perspectives of the managers of each university pillar about the teaching participation in the university tripod. When it comes to the methodology, the research has a qualitative, exploratory and descriptive nature, conducted through a case study with data triangulation approach through observation, document analysis and semi-structured interview applied with the seven main institutional managers responsible for decision making regarding the University tripod. The data about teaching distribution were processed using the Microsoft Excel® software and the data from the interviews were processed through content analysis. Here, the interviews were transcribed and inserted in the Atlas ti 8.4 software. Then, information was coded according to the approach of this research to create the networks and finalized with the analysis and discourse. The results show that the distribution of the teachers in the three university pillars is disproportionate: both in general and by campuses, it was verified that the teaching pillar has the largest number of teachers, followed by the research and extension pillar. When it comes to the perspective of managers about teacher participation, they considered that the number of teachers who dedicate themselves only to teaching activities is high; satisfactory when it comes to teachers involved in research activities; and low when referring to teacher dedicated to extension activities. The managers presented the existing difficulties in the current scenario and, even facing them, they believe that this reality can change (be improved), that is, the research and the extension activities may have a greater adhesion of teachers as long as there are internal and external investments